PERTIMBANGAN HAKIM DALAM PENJATUHAN HUKUMAN KEPADA PELAKU TINDAK PIDANA KORUPSI (Studi Putusan Nomor 03/Pid.Sus-TPK/2021/PN.Bdg) - Ivan Satriyani Bohalima (Jurnal Panah Hukum, 2022)
Corruption is an act carried out by abuse of power with the aim of enriching oneself or a corporation at the expense of state finances or the state economy. one of the corruption crimes that have been examined and tried by the Bandung District Court is the decision Number 03/Pid.Sus-TPK/2021/PN.Bdg.Types of research the method used is normative legal research with a statutory approach, a case approach and an analytical approach. Data collection was carried out using secondary data obtained through library materials consisting of primary legal materials, secondary legal materials and tertiary legal materials. The data analysis used is descriptive qualitative analysis and the conclusion is drawn using the deductive method. Based on the findings of the research and discussion, it can be concluded that the judge's considerations in imposing sentences to the perpetrators of criminal acts of corruption consist of juridical considerations of judges and non-juridical considerations of judges. So the judge sentenced him to 6 (six) years in prison will not provide a deterrent effect because the defendant as a Director who has great authority in the financial management of PT. Pos Properti Indonesia by violating Article 3 paragraph (1) in conjunction with Article 18 of Law Number 31 of 1999. The author suggests to law enforcement officials, the Panel of Judges who examines and decides on a corruption case, to be more careful in imposing the punishment imposed on perpetrators of corruption with the aim of creating a legal order that is in accordance with the goals of the Sta